1978
DOI: 10.1037/0022-0663.70.5.788
|View full text |Cite
|
Sign up to set email alerts
|

Effects of visual and auditory distractors on learning disabled and normal children's recognition memory performance.

Abstract: This research investigated whether distractibility in learning disabled children could be predicted on the basis of diagnosed visual and auditory learning deficits. Twenty-six children in Grades 2, 3, and 4 were classified as having visual or auditory reading disorders. They and 17 normally achieving children performed visual and auditory recognition memory tasks, with visual or auditory distractors presented on 80% of the trials. Analysis of error frequencies revealed that with distractors, children in the tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1980
1980
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Here high initial levels of activity and poor performance may have represented initial response uncertainty, which decreased over time. Control children have been previously noted to adapt to such initial difficulties faster (i.e., they show more rapid decreases in activity and errors) than do (a) hyperactive children (Zentall, Zentall, & Booth, 1978) and (b) learning disabled children (Patton & Offenbach, 1978). Hyperactive children may habituate more slowly to new, embedded, or unstructured stimuli and may habituate more rapidly to familiar predictable stimuli.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here high initial levels of activity and poor performance may have represented initial response uncertainty, which decreased over time. Control children have been previously noted to adapt to such initial difficulties faster (i.e., they show more rapid decreases in activity and errors) than do (a) hyperactive children (Zentall, Zentall, & Booth, 1978) and (b) learning disabled children (Patton & Offenbach, 1978). Hyperactive children may habituate more slowly to new, embedded, or unstructured stimuli and may habituate more rapidly to familiar predictable stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…For example, retarded children tended to be more active when presented recordings of spoken material at 80 dB (i.e., a reading of Pinnocchio) than when presented music of equivalent sound levels or during periods of silence (Reardon & Bell, 1970). Similarly, learning disabled children made more errors on recognition memory tasks in the presence of portions of a 60-dB children's story than did control children (Patton & Offenbach, 1978). Linguistic distractors (64-76 dB) disrupted the performance of suspected learning disabled children but not of control children (Lasky & Tobin, 1973).…”
mentioning
confidence: 90%
“…Roy (2009, p. 505) stated, "It's unusual for students not to be around music; she explains that this is true because of the increased availability of portable music devices and free music on the interne." Most students play music while studying (Patton and Offenbach, 1978). Anderson and Fuller, 2010, found that about 70% of students listen to music while studying.…”
Section: Introductionmentioning
confidence: 99%